Edukasi Dini Pajak kepada Calon Wajib Pajak - Suparmin; Satiman; Edon Ramdani (Abdimisi, 2025)
The largest component of state revenue is the tax sector. Tax revenue contributed 82.1% to Indonesia's state revenue in 2024, up from approximately 77.5% the previous year. Taxes are the foundation of the modern state's mutual assistance system. Without tax contributions, the state would lose its primary means of providing basic services to its citizens. The Ministry of Finance noted that by the first semester of 2025, tax revenue had reached IDR 1,420 trillion, or approximately 58% of the annual target. However, on the other hand, untapped tax potential remains enormous. Research shows that Indonesia's tax gap still ranges from 6–9% of gross domestic product (GDP), meaning approximately IDR 1,300 trillion in potential taxes are lost annually due to non-compliance and an untapped informal sector. If this situation is allowed to continue, the country will experience a widening fiscal deficit, forcing the government to borrow more or cut public services. It is very difficult to achieve voluntary taxpayer awareness and concern if the definition of "tax" does not include the phrases "enforceable" and "coercive." Based on this background, we, the PKM group of the Management and Accounting Study Program, Faculty of Economics and Business, Pamulang University, were moved to conduct community service in order to increase tax awareness through tax socialization activities with the theme "Early Tax Education for Prospective Taxpayers". The target of this activity is prospective early age taxpayers. The purpose of this PKM activity is to instill awareness about taxes from an early age, which is expected to influence children's mindsets and create a sense of pride in taxes to help increase state revenue. We, the Unpam PKM Team, propose to hold early tax education socialization for prospective taxpayers, which is given to the Al Kamilah Foundation students located in the Bojongsari area, Depok, West Java. This activity is planned to be held on Sunday, October 5, 2025 offline at the school location on Jl. Serua Raya, Serua Village, Bojongsari District, Depok City, West Java 16517. This PKM activity is expected to provide understanding and awareness to participants regarding the importance of taxes for state revenue. We will present the results of this PKM in the form of an article which will then be published in a nationally accredited journal. Keywords: Tax, Socialization, Community Service, Prospective Taxpayers, Islamic Students